Effect of yarn winding tension on the Wool ComfortMeter value when testing yarns. Issue 11 (July 2015) - Naebe, Maryam; McGregor, Bruce A; Tester, David
A new technique of predicting the comfort properties of single jersey knitted fabrics by using the Wool ComfortMeter to assess the corresponding yarns was previously investigated. In this study, the effect of the tension with which the yarn is wound on the Wool ComfortMeter yarn test plate was studied using 20 worsted, wool yarns comprising both one and two plies. The yarns covered a mean fiber diameter range from 13.8 to 24.3 µm. Three different levels of tension were applied to the yarn: 0 N (no applied tension); 0.245 N; and 0.735 N. The results, analyzed using multiple regression modeling, confirmed the significant effect of yarn tension on the Wool ComfortMeter value of the yarn, where yarn ply was also significant. The best predictor of the fabric Wool ComfortMeter value was using yarn winding with no applied tension. These results also showed that when the yarn Wool ComfortMeter values are available the mean fiber diameter provided little or no extra value in predicting fabric Wool ComfortMeter values. The models also detected significant effects from yarn count, yarn ply and fabric mass per unit area on fabric Wool ComfortMeter values.